2014
DOI: 10.3109/00498254.2014.973470
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent inhibition of CYP3A4 by gallic acid in human liver microsomes and recombinant systems

Abstract: 1.Gallic acid is a main polyphenol in various fruits and plants. Inhibitory characteristics of gallic acid on CYP3A4 were still unclear. The objective of this work is hence to investigate inhibitory characteristics of gallic acid on CYP3A4 using testosterone as the probe substrate in human liver microsomes (HLMs) and recombinant CYP3A4 (rCYP3A4) systems. 2.Gallic acid caused concentration-dependent loss of CYP3A4 activity with IC50 values of 615.2 μM and 669.5 μM in HLM and rCYP3A4 systems, respectively. IC50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Some polyphenols also found in mango have been documented to interfere with or affect the functioning of the CYP system. In vitro studies have described that isolated mangiferin or a mango stem bark extract (MSBE; containing mangiferin, quercetin, gallic acid, and catechins) can inhibit the activities of CYP3A4 in primary human hepatocytes; however, these effects were observed at µg/mL levels, which starkly contrasts with the typical concentrations expected to be found within the gut [ 112 , 113 , 114 , 115 , 116 ]. Hence, it is uncertain whether described interactions are to be considered clinically relevant.…”
Section: Potential Interactions Of Mango Polyphenols With Intestinal and Hepatic Enzyme Systemsmentioning
confidence: 99%
“…Some polyphenols also found in mango have been documented to interfere with or affect the functioning of the CYP system. In vitro studies have described that isolated mangiferin or a mango stem bark extract (MSBE; containing mangiferin, quercetin, gallic acid, and catechins) can inhibit the activities of CYP3A4 in primary human hepatocytes; however, these effects were observed at µg/mL levels, which starkly contrasts with the typical concentrations expected to be found within the gut [ 112 , 113 , 114 , 115 , 116 ]. Hence, it is uncertain whether described interactions are to be considered clinically relevant.…”
Section: Potential Interactions Of Mango Polyphenols With Intestinal and Hepatic Enzyme Systemsmentioning
confidence: 99%
“…Pharmacokinetic analysis of screened targets presents a promising role of CU in drug formulations. It suggests that the CU component, gallic acid downregulates the expression of CYP3A4 and thereby delays the drug metabolism [28,29] that further increasing the drug retention time in the body, eventually may result in increases in gastrointestinal absorption of a drug. Another Cu component, p-cresol, and Thymol inhibits the activity of CYP1A2 and CYP2D6 [30,31] and exerts similar activity to gallic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have revealed that GA weakly and time-dependently inactivated CYP3A4 via its oxidative products, leading to more potential for toxicity of co-administered drugs (Stupans et al, 2002; Pu et al, 2015; Vijayakumar et al, 2015). Of note, CYP3A4 plays a key role in metabolic clearance of Nifedipine and Amlodipine in humans, which were commonly prescribed calcium channel blocker for the treatment of hypertension (Zhu et al, 2014; Wang X.F.…”
Section: Discussionmentioning
confidence: 99%